2-Aryl-3-(arylideneamino)-1,2-dihydroquinazoline-4(3H)-ones as inhibitors of cholinesterases and self-induced β-amyloid (Aβ) aggregation: biological evaluations and mechanistic insights from molecular dynamics simulations - Sukumaran, Sri Devi; Faraj, Fadhil Lafta; Lee, Vannajan Sanghiran; Othman, Rozana; Buckle, Michael James Christopher (Royal Society of Chemistry, 2018)
A series of 2-aryl-3-(arylideneamino)-1,2-dihydroquinazoline-4(3H)-ones were evaluated as inhibitors of acetylcholinesterase (AChE), butyrylcholinesterase (BuChE) and self-induced β-amyloid (Aβ) aggregation. All the compounds were found to inhibit both forms of cholinesterase (IC50 in the range 4-32 μM) with some selectivity for BuChE. Most of the compounds also showed self-induced Aβ aggregation inhibitory activities, which were comparable or higher than those obtained for reference compounds, curcumin and myricetin. Docking and molecular dynamics (MD) simulation experiments suggested that the compounds are able to disrupt the dimer form of Aβ.